ISOLASI DAN IDENTIFIKASI JAMUR MIKROSKOPIS PADA AMPAS SAGU (Metroxylon sagu Rottb.) SEBAGAI SUMBER BELAJAR BIOLOGI SMA - Herinda Mardin; Syamsul; Ilyas H. Husain; Muh. Nur Akbar (Jurnal Biogenerasi, 2022)
This study aims to isolate and identify the microscopic fungi found in sago pulp (Metroxylon sagu Rottb). The results of this study were used as a learning resource for high school biology class X on fungi. This research is a descriptive study that aims to obtain isolates of microscopic fungi isolated from sago pulp (Metroxylon sagu Rottb). After the microscopic fungi isolates were found, the identification process was carried out. The results of the identification of microscopic fungi were used as a source of high school biology learning in the form of LKPD and then tested the validity of the LKPD. The results showed that the type of microscopic fungi found in sago pulp (Metroxylon sagu Rottb) was from the Ascomycetes class, especially the Eurotiales order with the species name Aspergillus sp. and the learning resource is declared valid with a CVI value of 1.00 so it is suitable to be used as a source of learning biology on fungi in class X high school.